Potential of cassava peel collected from Bauchi (Nigeria) as culture media for growing specific fungi - Yusuf Yahaya Miya; Thomas Murma Butuwo; Jamil Hassan Abdulkareem (Journal of Emerging Science and Engineering, 2024)
The objective of this paper is to assess the potential of using cassava peel for A. niger and penicillium growth using standard methods and chemicals of analytical grade. The result of the study indicates that, the peel is rich in proximate contents as the analyzed cassava peel is composed of 8.70% moisture, 4.89% crude protein, 6.9.00% carbohydrates, 4.00 % fat content, 8.93% ash, and 8.75% fibre. Considering the observed morphological and physical characteristics of the test fungi; therewith, A. niger, and penicillium were present. There is indication that, the two utilized media (control and formulated media) are in support of the two microbes growth and depicted positive results of degradation, as well as fermentation ability on the cassava peels. The enriched cassava agar supports higher growth of the two analyzed microbes (viz, A. niger, and penicillium). There was significant difference pertaining the colonies number made on the formulated media (cassava peel agar, and enriched cassava agar). Potato dextrose agar (PDA) shows lower colony count amounting to 3.4 0.1 CFU/ml for A. niger, and amounting to 3.3 0.2 CFU/ml for penicillium. Cassava peel agar (CPA) possessed 6.5 0.5 CFU/ml mean colony count (MCC) for A. niger, and 5.6 0.1 CFU/ml for penicillium. Enriched cassava agar media (ECA) had highest MCC as 7.8 0.1 CFU/ml with respect to A. niger, and 7.3 0.6 CFU/ml pertaining penicillium. Utilization of cassava peel as substrate due to its contents of nutrients that can meet the nutritional requirement of fungi growth is a better move. The peel may be considered as substitute and alternative substrate for producing culture media to cultivate fungi and consequently reducing pollution.